The Impact of Managerial Ownership, Operating Cash Flow, and Sales Growth on Corporate Tax Avoidance - Halim, Kusuma Indawati; Novianty, Novianty (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study investigates the impact of managerial ownership, operating cash flow, and sales growth on corporate tax avoidance in energy sector firms listed on the Indonesia Stock Exchange from 2018 to 2022. The research is quantitative in nature and employs an associative approach. This study employs secondary data from 21 randomly selected companies, based on criteria including consistent listing on the Indonesian Stock Exchange during the research period and the publication of comprehensive financial statements. Data analysis was conducted utilising multiple linear regression via Stata software. The study's findings indicate that managerial ownership, operating cash flow, and sales growth have a partial positive impact on tax avoidance. These findings are consistent with agency theory, which holds that company actions, including tax policies, can be influenced by managerial ownership. The findings also show that financial considerations, like the availability of cash flow and sales growth are important drivers of tax avoidance.